Labor outsourcing in Brazil: an atypical contract that legitimizes the legal and social setback - Zbucka-Gargas, Marta; Iannotti da Rocha, Cláudio (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
Labor law reform in Brazil has fundamentally changed the archetype of labor law, both in terms of substantive law and procedural law, from an individual and collective perspective. The new regulations have introduced the normative regulation of outsourcing in Brazil, which was previously absent. The issue identified in the following article is: labor outsourcing resulting from the Labor Reform can be considered a Brazilian legal advance or failure. Practice shows that Law No. 13,429 lowered the level of labor rights and allowing outsourcing in the main business of the borrowing company, without equalizing rights between the employees.